Discursive Taboo in Community Discourse: Communication Competence and Biblical Wisdom - Morgan, Julie W. (Christian scholar's review, 2009)
Racial tension, homosexuality and abortion are just a few of the topics where communication can quickly devolve into harmful conflict instead of calm and/or respectful dialogue. In this essay Julie W. Morgan and Richard K. Olsen explore the role of dialogue within a Christian academic community. How does a Christian academic community address subjects that are perceived as taboo? What happens in a Christian community that must confront issues or subjects that are “undiscussable”? While using an example on one campus to deconstruct a controversial incident, this study addresses the critical questions above and others pertaining to the processes that faith communities use to address (or avoid) controversial topics that arise on campus. While issues such as prayer and inspiration that are unique to a faith community should be celebrated and integrated, there is no need to create a uniquely Christian theory of dialogue. The paper concludes by demonstrating the utility of existing models to both analyze and remediate the case that provided the catalyst for the study. Ms. Morgan is Associate Professor of Communication Studies at Eastern University and Mr. Olsen is Associate Professor of Communication Studies at the University of North Carolina at Wilmington.